The Digital Revolution in Healthcare: What is Health Informatics and Where Are the Career Opportunities? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The healthcare landscape is undergoing a profound transformation, driven by the exponential growth of data and the integration of advanced technology. This c...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Medical Ethics; Patient Care